Impatiens pinganoensis (Balsaminaceae), a new species from Angola - Abrahamczyk, Stefan; Janssens, Steven; Xixima, Lázaro; Ditsch, Barbara; Fischer, Eberhard (Phytotaxa, 2016)
A new species, Impatiens pinganoensis is described from northern Angola. It belongs to the Impatiens filicornu complex and is closely related to I. filicornu from western central Africa, but differs in the decurrent petiole base, developing into cork ridges at older stems, its flower shape, i.e. the upper lateral petals laterally overtopping the lower lateral petals and by its characteristic white flowers with the mauve centre and wing-like pattern on the upper lateral petals. A table with flower characters of all species of the I. filicornu complex is presented for comparison. Additionally, some observations on the pollination and seed distribution are reported.